Difference in activated partial thromboplastin time values with two different reagents according to C-reactive protein values - Ishihara, Yuya; Doi, Hiroki; Sato, Seiko; Ito, Hiroyasu (Laboratory medicine, 2025)
Activated partial thromboplastin time (APTT) is susceptible to reagent composition. This study aimed to investigate a large number of specimens and determine the cause of discrepancies. This study included 18,994 subjects who underwent coagulation tests at our hospital from May 2020 to December 2020. Measuring reagents included HemosIL SynthASil APTT (APTT-SS, Instrumentation Laboratory) and Coagpia APTT-N (APTT-N, Sekisui Medical). A total of 451 patients demonstrated APTT-N of >39 seconds and an APTT-N/SS ratio of >1.3. A C-reactive protein (CRP) level of ≥1.4 mg/L demonstrated a significant positive correlation, with a higher APTT-N/SS indicating higher CRP levels. All 28 subjects receiving no anticoagulants and who had remaining specimens underwent a cross-mixing test (CMT). Of them, 17 were suspected for lupus anticoagulant (LA) by both the waveform shape and the index of circulating anticoagulant (ICA) value, 6 by the ICA value, and 5 were difficult to determine. This study revealed that the APTT-N prolongation correlated with CRP degree and the transient involvement of LA in CMT results due to CRP. This study indicated various reactivities depending on the assay reagents used. Further testing is warranted if LA is suspected, considering the patient's background.